Analisis Perbedaan antara Perencanaan dan Kebutuhan Tenaga Kerja Aktual menggunakan Metode DMAIC untuk Produk Bottle dan Cap - Martin Theo Purnomo; Prayonne Adi (Jurnal Titra, 2021)
This research was conducted to analyze the causes of the differences between planning and actual labor requirements for Bottle and Cap products at PT X. Planning for manpower requirements were calculated through SAP software, while the actual labor requirements were carried out by manual calculation of production process requirements. Analysis of the causes of the problem is carried out using the Define, Measure, Analyze, Improve, and Control (DMAIC) method. The DMAIC method is a method commonly used in Six Sigma to solve problems. After doing the analysis, it is found that the differences that occur are caused by changes in people's needs from the time of planning to the actual production. Changes in people's needs are caused by production problems (reject, downtime, and loss hour), and improper planning. So that the root cause of the difference in planning and actual productivity is; machine failure or worker error, as well as outdated planning data.